Analysis of the impact of land management options in tackling land degradation in sub-Saharan Africa example study based on long-term remote sensing and climate data - Le, Quang Bao; Sileshi, Gudeta W.; Kizito, Fred; Bossio, Deborah A.; Vlek, Paul L.G. (2017)
Tackling land degradation and restoring degraded landscapes requires information on areas of priority intervention since it is not economically and technically possible to manage all areas affected Recent developments in data availability and improved computation power have enhanced our understanding of the major regional drivers of land degradation and possible remedial measures at different scales In this study we used the land degradation hotspots identified using satellite and climate data covering the period 19822003 Vlek et al 2010 and simulated the potentials of different management measures in tackling land degradation in sub-Saharan Africa.